Aquatic environmental risk assessment for human use of the old antibiotic sulfamethoxazole in Europe. (22nd May 2015) - Straub, Jürg Oliver
Abstract: Sulfamethoxazole (SMX) is an old sulfonamide antibiotic that was launched first in combination with trimethoprim in 1969 by F.Hoffmann‐La Roche. Although sales figures for SMX have been declining over the past 20 yr, the compound is still widely used; moreover, many measured environmental concentrations (MECs) are available from Europe, the United States, Asia, Australia, and Africa. To assess aquatic risks of SMX in Europe, the exposure of European surface waters was predicted based on actual sales figures from IMS Health, incorporating environmental fate data on one side, and based on collated MECs representing more than 5500 single measurements in Europe on the other. Environmental effects were assessed using chronic and subchronic ecotoxicity data for 16 groups of aquatic organisms, from periphyton communities to cyanobacteria, algae, higher plants, various invertebrates, and vertebrates. Predicted no‐effect concentrations (PNECs) were derived using both deterministic and probabilistic methodology. The predicted environmental concentration (PEC)/PNEC and MEC/PNEC comparisons overall showed no appreciable risk, except in a low incidence (<0.55%) of cases in which exceptionally high MECs led to MEC/PNEC risk characterization ratios greater than 1. The PNECs derived in the present study can be used to extend aquatic environmental risk assessment for SMX to other continents. No risk appears for indirect human exposure to SMX via the environment. Environ Toxicol Chem 2016;35:767–779. © 2015 SETAC